(3UjZ GdYbhO hGdEjbGYGJs - (3GdcQcj GdYGedj, CHh GdMSf, GdeMbb GdKGfj, GdeMbb GdKGfj, Ydj Hf GdMSjf Hf YHO GdYGdj GdcQcj GdYGedj, J (B940(3g` (B1534(3es ((3GdeTgO GdZQhejs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg cKjQG ceG gh Cgdg (B... (3agPg LedI cGadI HHjGf UjZ GdYbhO hGdGjbGYGJ EP cGf dGHO ef eYQaJgG def GMJGL Edi TjA ef Gdecdajf dJhba MUhd GdCehQ GdeWdhHIs
(3BNQgG (B:s
(3BNQgG(B: (3hdh CbQ HdaX eHge agh CfhGY hdh GSJKfi aj GdebQHI adg CbSGe hCMcGe hLejY Pdc ePchQ aj eYGOfg ef cJH GdCUMGH adjWdH aj gfGc (B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L(B4: 281s
(3GdPQjYI, L (B15: 79s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis